THE SHAPE OF THE LEMURU FISH MARKET IN TERMS OF MARKET STRUCTURE ANALYSIS (CASE STUDY IN MUNCAR SUBDISTRICT, BANYUWANGI REGENCY, EAST JAVA) - Aditya Bagus Wicaksana; Budi Setiawan; Abdul Wahib Muhaimin (Socio-Economics/Agribusiness Department, 2022)
This study aims to analyze the structure of the Lemuru fish market that was formed in Muncar District, Banyuwangi Regency. There are two groups of respondents, fishermen (61 people) and marketing agencies (25 people). The sampling method used random sampling and slovin calculations to determine the number of fishermen respondents, the sample of marketing institutions used the snowball sampling method. To determine the market structure, the analysis used is the identification of the number of marketing institutions, market concentration using market share and CR4, product differentiation, and barriers to market entry. The results show that there are two marketing channels. Marketing channel one consists of 50 fishermen, five collectors, and seven retailers. Channel two consists of 11 fishermen and 13 retailers. From the analysis of market concentration using market share and CR4 at the fisherman and retailer level, a perfect competition market and a monopoly competition market at the collector level are formed. There is no product differentiation made by fishermen, collectors, and retailers. The barriers to entry and exit from the market faced by fishermen are natural and non-natural barriers, while collectors and retailers face non-natural barriers.